Materials structure & micromechanics of fracture VII selected, peer reviewed papers from the 7th International Conference on Materials Structure & Micromechanics of Fracture (MSMF-7), July 1-3, 2013, Brno, Czech Republic - Šandera, Pavel 1954- (Key engineering materials, 2013)
This volume contains paper selected from more than 230 contributors presented during the conference " Materials structure & micromechanics of fracture VII :selected, peer reviewed papers from the 7th International Conference on Materials Structure & Micromechanics of Fracture"